The impact of selected macro variables on child labor in Indonesia / Shafinah Rahim and Fatin Nur Nadia Bakar - Rahim, Shafinah; Bakar, Fatin Nur Nadia (Universiti Teknologi Mara Selangor, 2017)
This study investigates the impact of government expenditure, household expenditure and adult unemployment on child labour in Indonesia between 1985 and 2014. The data from the World Bank Indicators tested using Johansen & Juselius Cointegration (J&J), Vector Error Correction Model (VECM), Granger Causality, Generalized Variance Decomposition (GVDCs) and Generalized Impulse Response Functions (GIRFs) show thatthere are long run and short run relationships between the variables. Hence,the need to improve on policies relating to encouraging children to attend school without affecting their family income becomes critical. In addition household consumption pattern and spending decisions may require adjustment with the support of the authorities so as to assist the common man in prioritising their basic development needs, especially education.